Tensile deformation behavior of a near-α titanium alloy Ti-6Al-2Zr-1Mo-1V under a wide temperature range - Fang Hao; Junfeng Xiao; Yong Feng; Yue Wang; Jiantou Ju; Yuxuan Du; Kaixuan Wang; Li’nan Xue; Zhihua Nie; Chengweng Tan (Journal of Materials Research and Technology, 2020)
Isothermal tensile tests have been performed to study the mechanical evolution of Ti-6Al-2Zr-1Mo-1V titanium alloy under a wide temperature range from −60 ℃ to 900 ℃ and a strain rate of 10−3 s-1. Electron backscatter diffraction (EBSD) tests were used to analyze the evolution of microstructure and deformation mechanisms under different temperatures. The results indicate that deformation mechanisms vary with the deformation conditions. At relatively low temperatures, −60 ℃, 23 ℃, and 400 ℃, dislocation slips mechanism dominates the deformation, even though tensile twinning is detected. While globularization of α laths and dynamic recrystallization (DRX) are dominant at high temperatures, 600 ℃ and 800 ℃, resulting in the flow softening. During the deformation under different temperatures, the β phase plays a crucial role in accommodating deformation between α and β phase by migration of grain boundaries and rotation of grain, leading to a dramatically change in texture of β phase.